Dimension of Multicultural Education: Issues for School Reform in Nepal - Mahat, Dhana Krishna (Sotang, Yearly Peer Reviewed Journal, 2019)
Multicultural education is very important and necessary concept. It is an educational approach designed to ensure equal educational opportunities for all students, including those in marginalized groups. Multicultural issue in the present context is a global issue of socialization. It has not yet been materialized into the education system in Nepal. The education system of a country should prepare students to function in today’s diverse society. There are issues emerging in the electiveness of the multicultural education and the concerns how to better shape the multicultural classroom in Nepal. There are many views on the benefits and/or shortcomings of the multicultural education. The question is not whether a multicultural education should be adopted but it is rather what we understand from multicultural education and how we are going to initiate such a reform within an educational system. In this article, the five dimensions of multicultural education and issues of school reform are described in the Nepalese context.